Studies of agronomic properties of mine tailings using compost - Hang Leakhena (2009)
The aim of this study is to determine the effect on the remobilization of heavy metals and enhancement of the cultivation potential of mine tailing by compost addition and phytoremediation. The study utilized mine tailings from selected from sites in the Philippines particularly Copper-Gold mining areas. Mine tailing were mixed with composts at different weight ratios: (percent of mine tailings / percent of compost) 50/50, 60/40, 70/30, 80/20, 90/10 and re vegetated with wild cabbage ( Brassica Oleracea L.) plants by pot experiment. The removal efficiency of Cu, Zn, Mn, and Fe from contaminated soils was studied. For validation, the plant tissues were analyzed for the concentration of Cu, Zn, Mn, and Fe. The compost/mine tailings mixtures were analyzed for cultivation potential.